2022
DOI: 10.1007/s12031-022-02068-w
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Common Pathogenic Mechanisms of COVID-19 and Parkinson Disease: An Integrated Bioinformatics Analysis

Abstract: Coronavirus disease 2019 (COVID-19) has emerged since December 2019 and was later characterized as a pandemic by WHO, imposing a major public health threat globally. Our study aimed to identify common signatures from different biological levels to enlighten the current unclear association between COVID-19 and Parkinson's disease (PD) as a number of possible links, and hypotheses were reported in the literature. We have analyzed transcriptome data from peripheral blood mononuclear cells (PBMCs) of both COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…We predicted TFs that might interact with three hub genes using TF hub gene regulatory networks. Among them, ERG, ZFX and SOX2 have been reported to be highly associated with tumor development ( Baldus et al, 2006 ; Jahanimoghadam et al, 2022 ; Schmoellerl et al, 2023 ; Wang et al, 2023 ). The development of tumors in DM patients may be associated with these TFs, however, no relevant reports are available at present, and further investigation is required to confirm and demonstrate this association in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted TFs that might interact with three hub genes using TF hub gene regulatory networks. Among them, ERG, ZFX and SOX2 have been reported to be highly associated with tumor development ( Baldus et al, 2006 ; Jahanimoghadam et al, 2022 ; Schmoellerl et al, 2023 ; Wang et al, 2023 ). The development of tumors in DM patients may be associated with these TFs, however, no relevant reports are available at present, and further investigation is required to confirm and demonstrate this association in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Jahanimoghadam et al describe the interactions of common DEGs by constructing a protein interaction network, in which C1QA is one of the core ceRNA regulators. They find that IF135, MX1, SPI1 and IF144L associated with it are in the periodontitis core PPI network, and C1QB in the periodontitis core ceRNA network ( Jahanimoghadam et al, 2022 ). Wang et al construct the PPI network of differential genes when studying the changes in gene expression profiles in the dorsal horn of the spinal cord after sciatic nerve injury, and C1QA plays a more central role in this network.…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise the possibility that an infection could affect synucleinopathy and by extension the progression of PD. A complementary study that used bioinformatics also found a connection between SARV-COV-2 and PD through, among other things, the microglia pathogen phagocytosis pathway and microglia activation, which was suggested to have been significant in the onset or progression of PD [ 83 ]. In a similar vein, AD and COVID-19 share multiple risk factors and pathogenic pathways that may contribute to the acceleration of neurodegenerative processes in AD patients infected with the virus [ 84 ].…”
Section: Discussionmentioning
confidence: 99%